Visual acuity improvements after implantation of toric intraocular lenses in cataract patients with astigmatism: a systematic review - Agresta, Blaise; Knorz, Michael C.; Donatti, Christina; Jackson, Daniel (BMC ophthalmology, 2012)
Cataracts are a common and significant cause of visual impairment globally. We aimed to evaluate uncorrected distance visual acuity (UDVA) as an outcome in treating astigmatic cataract patients to assist clinicians or ophthalmologists in their decision making process regarding available interventions.
Published: 15 August 2012
Gesehen am 22.06.2018